Potensi Pengembangan Desa Wisata di Desa Pakuan Kabupaten Lombok Barat - Kurniawan, Agus; Hirsan, Fariz Primadi; Ridha, Rasyid; Yuniarman, Ardi (P4W IPB, 2025)
This study was conducted to identify and develop the tourism potential in Pakuan Village, Narmada Subdistrict, West Lombok Regency, West Nusa Tenggara. The village holds significant potential to become a leading tourist destination, particularly through its natural wealth, such as waterfalls and forests, as well as its unique cultural heritage. The research employs a qualitative descriptive approach to thoroughly describe the potential for developing tourist attractions and natural resources in Pakuan Village. Through field observations, in-depth interviews, and documentation, the study reveals several key barriers to tourism development, including limited accessibility and inadequate supporting infrastructure. However, there is a substantial opportunity to develop this village as a sustainable tourism destination by involving the local community in tourism management and leveraging government support. The results of the study indicate that community-based tourism development and environmental conservation are crucial to ensuring the preservation of Pakuan Village's natural and cultural heritage. Recommendations for improving accessibility, strengthening infrastructure, and enhancing promotion and marketing are suggested to optimize the village's tourism potential. The proposed strategies will contribute to improving the well-being of the local community and creating an engaging and sustainable tourist experience for visitors. The outcomes of this research include a publication in a nationally accredited Sinta journal with a minimum ranking of 3 and its use as teaching material.